2022
DOI: 10.1016/j.lana.2021.100167
|View full text |Cite
|
Sign up to set email alerts
|

Why should obese youth be prioritized in COVID-19 vaccination programs? A nationwide retrospective study

Abstract: Background The dominant effect of age on COVID-19 mortality obscures the impact of other risk factors. Although the elderly is at a greater risk of severe disease and death due to COVID-19, the interaction of obesity and age was not carefully assessed. This analysis is especially critical for prioritizing groups to receive COVID-19 vaccination. Methods Starting with 1,120,767 unvaccinated individuals registered in a Brazilian surveillance system, we selected 313,898 hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 17 publications
4
23
0
Order By: Relevance
“…We showed death in patients with overweight and obesity compared to normal weight, confirming that overnutrition is a risk factor for coronavirus disease. These data corroborate a recent retrospective study confirming obesity as an independent risk factor for COVID-19 severity [10]. We hypothesized that the differences related to plasmatic urea concentrations may be due to the increased age in normal weight patients, once in our population the patients with obesity were significantly younger.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We showed death in patients with overweight and obesity compared to normal weight, confirming that overnutrition is a risk factor for coronavirus disease. These data corroborate a recent retrospective study confirming obesity as an independent risk factor for COVID-19 severity [10]. We hypothesized that the differences related to plasmatic urea concentrations may be due to the increased age in normal weight patients, once in our population the patients with obesity were significantly younger.…”
Section: Discussionsupporting
confidence: 91%
“…The literature reveals that laboratory analysis of obese patients with COVID-19 embrace variations such as higher C-reactive protein count, lower lymphocyte count, lower platelet count, higher levels of hemoglobin, CK, creatinine and, LDH [7,8]. Similar to our data, some studies have already demonstrated that obesity is an important risk factor among young people, suggesting a positive correlation between higher BMI, the severity of the disease, and mortality risk [9,10].…”
Section: Discussionsupporting
confidence: 87%
“… 15 , 16 , 17 , 18 Thereby, several reports recommended prioritization of obese people to obtain COVID‐19 vaccination. 11 , 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, infected people with obesity (particularly those under 60 years of age) are more likely to require acute care, admission to the intensive care unit, intubation, and mechanical ventilation 3 . Even young patients are at higher risk for a nonfavorable COVID-19 prognosis if they suffer from metabolic dysfunctions 4 5 . Children usually develop an asymptomatic to moderate infection causing few hospitalizations; but a recent meta-analysis indicates that even childhood obesity is likely to increase the risk of severe COVID-19 6 .…”
Section: Introductionmentioning
confidence: 99%